Stock photos of the Medford/Somerville campus, including the ASEAN Auditorium, the Jumbo statue, inside Tisch Library, construction on the roof of the Campus Center, and Goddard Chapel. Photo 024 - Loeb, Brian (Tufts Archival Research Center, 2008)
Stock photos of the Medford/Somerville campus, including the ASEAN Auditorium, the Jumbo statue, inside Tisch Library, construction on the roof of the Campus Center, and Goddard Chapel.